Influence of heating treatment and membrane concentration on the formation of soluble aggregates. (October 2015) - Li, Y.; Dalgleish, D.; Corredig, M.
Abstract: This study investigated the effect of thermal denaturation on milk concentrated by ultrafiltration (UF) with or without diafiltration (DF) at various time–temperature combinations. The non-sedimentable protein fractions present in milk after heating were analyzed using size exclusion chromatography and their composition was determined. The extent of whey protein denaturation and the composition of the soluble complexes depended not only on heating temperature and time, but also on the protein concentration. There was a greater extent of protein aggregation in concentrated milk compared to 1 × milk, and there was a significant difference in the size and composition of the aggregates present in the non-sedimentable fraction depending on whether the milk was concentrated only by UF or if DF was also used. DF milk contained a higher concentration of non-sedimentable protein compared to UF milk. In all samples, κ -casein and β -lactoglobulin were the main proteins present in the soluble aggregates, but higher temperatures and longer heating times resulted in greater extents of denaturation of α -lactalbumin. This work clearly identified differences in the extent of aggregation between milk concentrated by UF or UF and DF, and unconcentrated milk, with important consequences on the processing functionality of caseins. Highlights: Diafiltration causes higher aggregation than ultrafiltration Complexes in concentrated milk contain more α-lactalbumin Concentrated milk has more soluble caseins than skim milk Composition of the aggregates depend on concentration, mode of concentration and time/temperature